Anticholinergic drug use and risk of mortality for people with dementia in Northern Ireland. (3rd August 2021) - McMichael, A. J.; Zafeiridi, E.; Ryan, M.; Cunningham, E. L.; Passmore, A. P.; McGuinness, B.
Abstract: Objective: Anticholinergic burden refers to the cumulative effect of medications which contain anticholinergic properties. We assessed how anticholinergic burden and different types of anticholinergic medications influence mortality rates among people with dementia in Northern Ireland. Our secondary aim was to determine what demographic characteristics predict the anticholinergic burden of people with dementia. Methods: Data were extracted from the Enhanced Prescribing database for 25, 418 people who were prescribed at least one dementia management medication between 2010 and 2016. Information was also extracted on the number of times each available anticholinergic drug was prescribed between 2010 and 2016, allowing the calculation of an overall anticholinergic burden. Cox proportional hazard models were used to determine how anticholinergic burden influenced mortality whilst multilevel model regression determined what demographic characteristics influence overall anticholinergic burden. Results: Of the 25, 418 people with dementia, only 15% ( n  = 3880) had no anticholinergic burden. Diazepam (42%) and risperidone (18%) were the two most commonly prescribed drugs. Unadjusted Cox proportional hazard models indicated that higher anticholinergic burden was associated with significantly higher mortality rates in comparison to people with dementia who had no anticholinergic burden (HR = 1.59: 95% CI = 1.07-2.36). In particular, urological (HR = 1.20: 95% CI = 1.05-1.38) and respiratory (HR = 1.17: 95% CI = 1.08-1.27) drugs significantly increased mortality rates. People with dementia living in areas with low levels of deprivation had significantly lower anticholinergic burden (HR=-.39: 95% CI=-.47:-30). Conclusions: Reducing anticholinergic burden is essential for people with dementia. Further research should address the unfavourable prognosis of people living with dementia in highly deprived areas.